2017
DOI: 10.1002/pds.4228
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life patterns of use, safety and effectiveness of sunitinib in first‐line therapy of metastatic renal cell carcinoma: the SANTORIN cohort study

Abstract: Results from this large observational study suggest that effectiveness of sunitinib in first-line mRCC as predicted by clinical trials is maintained in real-life clinical practice. The expected benefit in poor-prognosis patients that were not evaluated in the pivotal clinical trial remains; however, questionable and long-term safety monitoring is still warranted. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Performance or risk status can have a dramatic effect on survival outcomes and may account for some of the variation in reported survival outcomes. Sunitinib efficacy outcomes reported by Schnadig et al and Noize et al were generally lower than those reported in RCTs and our combined confidence estimates; however, there were greater numbers of poor-risk patients and fewer favorable-risk patients in these studies compared with RCTs [44,47]. An RWD study by Rini [31].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Performance or risk status can have a dramatic effect on survival outcomes and may account for some of the variation in reported survival outcomes. Sunitinib efficacy outcomes reported by Schnadig et al and Noize et al were generally lower than those reported in RCTs and our combined confidence estimates; however, there were greater numbers of poor-risk patients and fewer favorable-risk patients in these studies compared with RCTs [44,47]. An RWD study by Rini [31].…”
Section: Discussionmentioning
confidence: 48%
“…RWD studies used a variety of sources to extract data, including national and local cancer registries, insurance databases, pharmacy databases, and patient medical records [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Studies were from a wide range of countries, including USA, Canada, Australia, Spain, France, Greece, Italy, Netherlands, Czech Republic, China, Japan, Korea, and India.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Currently, the most commonly used agents are the tyrosine kinase inhibitors sunitinib and pazopanib, for the first-line treatment of mRCC patients with good or intermediate prognosis [7] stratified by MSKCC risk criteria based on phase III clinical trials [16,17]. The effectiveness and tolerability of both agents have been confirmed by real-world studies [18,19]. Everolimus and axitinib emerged as safe and effective second-line treatment options for mRCC patients after progression on VEGFtargeted therapy [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of sunitinib in treatment‐naive patients with advanced clear cell RCC was demonstrated in the pivotal phase III trial, in which sunitinib significantly prolonged median progression‐free survival (mPFS) but not overall survival (OS) versus IFN‐α (Table ). Several real‐world studies confirm the effectiveness of first‐line sunitinib in patients with aRCC . Most large ( n > 150) real‐world studies are retrospective, multicenter analyses with a wide range in mPFS (7.0–20.0 months) and median OS (mOS; 18.7–45.1 months) reported across studies .…”
Section: Introductionmentioning
confidence: 94%
“…Several real‐world studies confirm the effectiveness of first‐line sunitinib in patients with aRCC . Most large ( n > 150) real‐world studies are retrospective, multicenter analyses with a wide range in mPFS (7.0–20.0 months) and median OS (mOS; 18.7–45.1 months) reported across studies . In one of the larger real‐world sunitinib studies that provided information about the effectiveness in patient subgroups often excluded from clinical trials, an expanded‐access trial in 4,543 patients with metastatic RCC demonstrated that the objective response rate (ORR) was 16% and mPFS and mOS were 9.4 and 18.7 months, respectively .…”
Section: Introductionmentioning
confidence: 99%